2020
DOI: 10.1093/ofid/ofaa433
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Cardiac Implantable Electronic Device–Related Infection in Patients With Cancer: The Role of a Comprehensive Prophylactic Bundle Approach That Includes the Antimicrobial Mesh

Abstract: Background Oncological patients have several additional risk factors for developing a cardiac implantable electronic device (CIEDs)-related infection. Therefore, we evaluated the clinical impact of our comprehensive bundle approach that includes the novel minocycline and rifampin antimicrobial mesh (TYRX) for the prevention of CIED infections in patients living with cancer. Methods We retrospectively reviewed all consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Therefore, selecting a high‐risk population for infection, such as an oncological population with several risk factors, would likely decrease the number needed to treat and improve the cost effectiveness of the envelope, which is priced slightly below $1000 106,107 . At our institution, all patients who have cancer receive the TYRX envelope as part of a comprehensive prophylactic bundle, which has been demonstrated to be both safe and effective in maintaining a low rate of CIED infection (1.3%) and is well within published averages in the broader population of all CIED recipients 108 …”
Section: Specific Device‐related Recommendationsmentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore, selecting a high‐risk population for infection, such as an oncological population with several risk factors, would likely decrease the number needed to treat and improve the cost effectiveness of the envelope, which is priced slightly below $1000 106,107 . At our institution, all patients who have cancer receive the TYRX envelope as part of a comprehensive prophylactic bundle, which has been demonstrated to be both safe and effective in maintaining a low rate of CIED infection (1.3%) and is well within published averages in the broader population of all CIED recipients 108 …”
Section: Specific Device‐related Recommendationsmentioning
confidence: 62%
“…106,107 At our institution, all patients who have cancer receive the TYRX envelope as part of a comprehensive prophylactic bundle, which has been demonstrated to be both safe and effective in maintaining a low rate of CIED infection (1.3%) and is well within published averages in the broader population of all CIED recipients. 108 Of note, few studies have evaluated novel techniques for decreasing microbial adherence to CIEDs. Polyurethane has been shown to have a higher affinity for biofilm-producing pathogens than titanium in vitro.…”
Section: Cardiac-implantable Electronic Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated a non-increased risk of CIED infections within an oncologic population, including patients with solid and hematologic tumors. As such, it was concluded that there is no compelling justification for withholding the placement of a CIED from oncological patients solely on the grounds of infection risk [ 18 ].…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…The comprehensive bundle approach that recommends the use of novel minocycline and rifampicin antimicrobial mesh (TYRX) to prevent the IAIs in patients suffering from both solid organ and hematologic malignancies with CIED was reported recently [ 39 ]. Such an approach was previously confirmed as an important strategy to prevent cardiac IAIs as evidenced by the results of the Worldwide Randomized Antibiotic Envelope Infection Prevention Trial (WRAP-IT).…”
Section: Reviewmentioning
confidence: 99%